A new solution to the purchasing power parity puzzles: Risk-aversion, exchange rate uncertainty and the law of one price - Michael G. Arghyrou; Andros Gregoriou; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2009)
We argue that even in perfectly frictionless markets risk aversion driven by exchange rate uncertainty may cause a wedge between the domestic and foreign price of a totally homogeneous good. We test our hypothesis using a natural experiment based on a unique micro-data set from a market with minimum imperfections. The empirical findings validate our hypothesis, as accounting for exchange rate uncertainty we are able to explain a substantial proportion of deviations from the law of one price. Overall, our analysis suggests the possibility of a new solution to the purchasing power parity puzzles.
Keywords: F31; F41; 330; law of one price; purchasing power parity; risk aversion; exchange rate uncertainty; Kaufkraftparität; Internationaler Preiszusammenhang; Wechselkursrisiko; Risikoaversion; Industriestaaten